On the Hybrid Power Mean Involving the Character Sums and Dedekind Sums - Xiaoling Xu (Journal of Mathematics)
The main purpose of this paper is to use the elementary and analytic methods, the properties of Gauss sums, and character sums to study the computational problem of a certain hybrid power mean involving the Dedekind sums and a character sum analogous to Kloosterman sum and give two interesting identities for them.